2017
DOI: 10.1038/nn.4580
|View full text |Cite
|
Sign up to set email alerts
|

Sensory integration and neuromodulatory feedback facilitate Drosophila mechanonociceptive behavior

Abstract: Nociception is an evolutionary conserved mechanism to encode and process harmful environmental stimuli. Like most animals, Drosophila larvae respond to a variety of nociceptive stimuli, including noxious touch and temperature, with a stereotyped escape response through activation of multimodal nociceptors. How behavioral responses to these different modalities are processed and integrated by the downstream network remains poorly understood. By combining transsynaptic labeling, ultrastructural analysis, calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
180
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(196 citation statements)
references
References 83 publications
(122 reference statements)
8
180
0
Order By: Relevance
“…Functional network analyses by these and additional studies have revealed a hierarchical network organization, multisensory integration, and modality and positionspecific network functions suggesting extensive processing and modulation of nociceptive inputs 18,24,29 . This system thus offers a unique opportunity to probe how CNS circuit growth is regulated while preserving specific connectivity and functional output.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…Functional network analyses by these and additional studies have revealed a hierarchical network organization, multisensory integration, and modality and positionspecific network functions suggesting extensive processing and modulation of nociceptive inputs 18,24,29 . This system thus offers a unique opportunity to probe how CNS circuit growth is regulated while preserving specific connectivity and functional output.…”
Section: Introductionmentioning
confidence: 80%
“…Recent studies have described a hierarchical circuit architecture and multisensory integration in the larval somatosensory network, which integrates the activity of distinct sensory subsets and determines specific behaviors by inhibition or facilitation 18,24,25,27,48 . While individual larval sensory neuron subsets have been shown to respond to specific modalities like vibration (cho) 70 , noxious cold (cho, C3da) 45,47 , gentle (C2da, C3da) 21,46 and harsh touch (C4da) 21,71 , overlap in 2 nd order neuron innervation also results in extensive sensory integration (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations